Pemanfaatan Travel Writing Sebagai Sumber Informasi Bagi Wisatawan Nusantara - Nikasius Sinangjoyo; Fian Damasdino (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2018)
The era of information and communication technology provides opportunities and convenience for tourists to meet their needs of self-actualization by telling their experiences through writing, so-called travel writing. Travel writing can be used as a source of information to guide some potential tourists in planning their travels. Furthermore, it can also increase the number of domestic tourists’ visit to several tourist destinations spread across the nation. This research, through the descriptive qualitative approach, aims to thoroughly describe the phenomenon of the use of travel writing as the source of travel information. The informants in this research were 7 people. The data were collected through in-depth interview and questionnaire. The research results shows that magazines, newspapers and web portals have high credibility, while travel blogs have an objective and reliable. There were 5 characteristics of travel writing which expected by the reader such as simple writing, clear language, photo display, facts, and have value of benefits